Evidence for Replacement of an Infected Synthetic by a Biological Mesh in Abdominal Wall Hernia Repair - Montgomery, Agneta; Kallinowski, Friedrich; Köckerling, Ferdinand (Frontiers in Surgery, 2016)
The incidence of deep infection using a synthetic mesh in inguinal hernia repair is low and reported to be well below 1%. This is in contrast to incisional hernia surgery where the reported incidence is 3% respective 13% comparing laparoscopic to open mesh repair reported in a Cochrane review. Main risk factors were long operation time, surgical site contamination and early wound complications. An infected mesh can be preserved using conservative treatment were negative pressure wound therapy (VAC®) could play an important role. If strategy fails, the mesh needs to be removed. This review aims to look at evidence for situations were a biological mesh would work as a replacement of a removed infected synthetic mesh. Material and Methods A literature search of the Medline database was performed using the PubMed search engine. Twenty publications were found relevant for this review. Results For studies reviewed three options are presented: removal of the infected synthetic mesh alone, replacement with either a new synthetic or a new biological mesh. Operations were all performed at specialist centers. Removal of the mesh alone was an option limited to inguinal hernias. In ventral/incisional hernias the use of a biological mesh for replacement resulted in a very high recurrence rate, if bridging was required. Either a synthetic or a biological mesh seems to work as a replacement when fascial closure can be achieved. Evidence is though very low. Conclusion When required, either a synthetic or a biological meshes seems to work as a replacement for an infected synthetic mesh if the defect can be closed. It is however not recommended to use a biological mesh for bridging. Mesh replacement surgery is demanding and is recommended to be performed in a specialist center.